Systematic revision of Entomobryidae (Collembola) by integrating molecular and new morphological evidence - Zhang, Feng; Deharveng, Louis (Zoologica scripta, 2015)
Entomobryidae, the largest collembolan family, is traditionally classified at suprageneric level using a limited set of morphological structures, such as scales, antennal segmentation. Most tribal and subfamilial delimitations appear, however, disputable in the light of recent works. Integrating molecular and morphological evidence, we propose here a revision of the systematics of the family. In addition to traditional taxonomic characters, tergal specialized chaetae (S‐chaetae) are newly introduced, and their patterns are shown to be diversified at all levels from species to subfamilies. S‐chaetotaxic pattern on phylogenetic tree shows that evolution of S‐chaetae is not parallel between the different terga and that their patterns coincide well with the known molecular phylogeny, providing a powerful tool for the systematics of Entomobryidae. Orchesellinae sensu Soto‐Adames et al. (Annals of the Entomological Society of America, 101, 2008, 501); is divided into three subfamilies: Orchesellinae s. s., Bessoniellinae and Heteromurinae, the latter two upgraded from the original tribal level. Entomobryinae sensu Szeptycki (Morpho‐Systematic Studies on Collembola. IV. Chaetotaxy of the Entomobryidae and its Phylogenetical Significance, 1979), is no longer divided into scaled and unscaled tribes, and Lepidosira‐group is transferred from Seirinae to Entomobryinae. A key to subfamilies and tribes and a comparison with previous classifications of the Entomobryidae are provided. This study greatly improves the understanding of primary and secondary characters and erects the fundamental framework for the taxonomy of Entomobryidae.